Analisis Kinerja Perusahaan BUMN ditinjau dari Kebijakan Privatisasi dan Good Corporate Govermance - Khairur Roziqinv (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2020)
Privatisation and Good Corporate Governance systems are government policies to improve the performance of state-owned enterprises (SOEs). The BUMN Ministry Road Map for 2015-2019 contains various policies from the SOE Ministry through the SOE restructuring and privatisation program. Sale of 49% shares of PT JICT, a subsidiary of PT Pelindo II or Indonesia Port Corporation II (IPC), to Hutchison Port Holding Group (HPH Group) with a value of USD 215,000,000, for 20 years and the remaining 51% of the shares are owned by IPC. Does it make the writer research that the privatisation process has fair value and follows the ministerial regulation of SOEs regarding Good Corporate Governance? The calculation and analysis of the company's projection of PT JICT are USD 262,490,000, - so that the sale of 49% shares to HPH Group is USD 215,000,000 below the fair value, with a difference of USD 47.49 million. Indicator of GCG implementation based on SK-16 / S.MBU / 2012 decision after the writer assessed PT JICT officials and employees of the privatisation process which scored 75.53 with several sub-standard indicators: Transparency, independence and Fairness that earned value ≤ 75 with unfavourable conclusions.